2017
DOI: 10.1002/2016jc012362
|View full text |Cite
|
Sign up to set email alerts
|

The impact of storms and stratification on sediment transport in the Rhine region of freshwater influence

Abstract: We present measurements of along and across‐shore sediment transport in a region of the Dutch coast 10 km north of the Rhine River mouth. This section of the coast is characterized by strong vertical density stratification because it is within the midfield region of the Rhine region of freshwater influence, where processes typical of the far‐field, such as tidal straining, are modified by the passage of distinct freshwater lenses at the surface. The experiment captured two storms, and a wide range of wind, wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 53 publications
(121 reference statements)
0
39
0
Order By: Relevance
“…The high concentrations observed during the WSGF resulted in elevated cross‐shore sediment transport (Figure d). The net cross‐shore sediment flux due to the WSGF event was an order of magnitude greater than the suspended load transport in the overlying water column (0.5 mab to the surface) measured nearby at the 12 m site (Flores et al, ) or the bedload transport based on the formula of Madsen () for the same time period (Figure d). In fact, the offshore transport during this 1.5‐day WSGF event was much higher than the suspended sediment transport observed during a 30‐day period at the nearby 12 m site.…”
Section: Observations and Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…The high concentrations observed during the WSGF resulted in elevated cross‐shore sediment transport (Figure d). The net cross‐shore sediment flux due to the WSGF event was an order of magnitude greater than the suspended load transport in the overlying water column (0.5 mab to the surface) measured nearby at the 12 m site (Flores et al, ) or the bedload transport based on the formula of Madsen () for the same time period (Figure d). In fact, the offshore transport during this 1.5‐day WSGF event was much higher than the suspended sediment transport observed during a 30‐day period at the nearby 12 m site.…”
Section: Observations and Resultsmentioning
confidence: 72%
“…While the emplacement of the Sand Engine undoubtedly provides a large source of coastal sediment, monitoring has shown that the particle size distribution around it has coarsened since its construction (Huisman et al, 2016). Moreover, observed suspended sediment concentrations are in the same range as those observed prior to its construction (Flores et al, 2017;Horner-Devine et al, 2017;van der Hout et al, 2015). This suggests that the Sand Engine does not provide a large source of fine sediments.…”
Section: Study Site and Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The orange circle represents a meteorological measurement station, and the star represents the location for discharge data. (c) Detailed schematic of the measurement setup (Figure after Flores et al, ). A third frame is placed at 12 m depth.…”
Section: Measurementsmentioning
confidence: 99%
“…Journal of Geophysical Research: Oceans, 123, 8460-8488. https://doi.org/10. 1029 in offshore or open ocean waters (e.g., Flores et al, 2017;Horner-Devine et al, 2015), estuaries are semienclosed (Cameron & Pritchard, 1963;Hansen & Rattray, 1965, 1966 and lagoons can be more limited in exchange with the coastal ocean (Kjerfve, 1986;Kjerfve & Magill, 1989) and may even have multiple openings (Duran-Matute et al, 2016;Herrling & Winter, 2015;Jia & Li, 2012;Li, 2013). The constrictions of such system at entrance can act as low-pass filters that diminish tidal influence into the basin (Fernandes et al, 2004) or change the fortnightly tidal phases (Hill, 1994).…”
Section: 1029/2018jc013985mentioning
confidence: 99%